Mineralogical Characterization of Rocks Composing the Volcanic Body that Crops Out near Town of Iza, Boyacá, Colombia. Petrography, Metallography and Elemental Analysis by Scanning Electronic Microscope - Contreras-Fayad, David Andrei; Jaramillo-Mejía, José María (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2010)
We present here the results of detailed analysis of four samples from the Iza Volcanic body. The analysis were done at Gmas* Laboratory using and array of tools available there: Optical microscopy for petrographic, and metallographic study of polished thin sections; a SEM with BSE, SE and EDAX allowed the elemental chemical composition of minerals present in the samples, and finally we use XRD for mineral identification.  The strong hydrothermal alteration of the Iza volcanic rocks was evident in the all the analyses that were carried out, we identified the presence of minerals as the tridymite, the opal, the chalcedony, epidote (pistacita), and alunite , this last mineral is usually replacing potassic feldspars. The metallographic study showed a prevalence of the pyrite and the rutile in relation to the total of metallic minerals in veins and its surrounding area. By means of the optical petrography and elemental analysis with the EDAX, it was possible the identification of the amphiboles. On the other hand, X-ray diffraction was of vital importance in determining the presence of sanidine (highly disordered). We also found that sanidine is not the only K2O rich phase on these volcanic rocks.